(untitled) (Research, Society and Development, 2021)
The objective of this research is to observe violence and female mortality due to external causes in the Metropolitan Region of Manaus (RMM), from 1996 to 2018 and its occurrences by ethnicity. The external causes observed here are related to accidents and aggressions that resulted in the deaths of Amazonian women in this time frame. The data come from the Datasus Mortality Information System (SIM / DATASUS). The results show that although the volume of mortality from accidents is significant, the deaths resulting from violence against women are higher. The conclusion is that there is a need to take measures that work together to minimize such great inequity.